Billing System for Karen’s Beauty Product: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research, entitled A Billing System for Karen’s Beauty Product, made to create andImplement a Computerize Billing Management System for Karen’s Beauty Product; the goalsof pursuing this research are to improve and enhance the daily process of storing Customers'borrower information and especially Calculation that can consume large digits and handlesimultaneously bought items, thus by creating efficiently managing Computation for Karen’sbeauty product.The outcome of the system was successful; it was properly implemented while theresearchers based the client problem, and all the contents of the system made by theresearchers were adapted to the expectation until it was made to become reality; this is helpfulin exchange for their manual process despite the creation of the system, the researchersshowed the dedication upon creating the system.The researchers implemented a user-friendly application that can provide security in securingimportant contacts of borrowers and especially Simultaneous Computation that can handlelarge digits to manage to calculate various bought products. Based on what the providedsystem can do, the system has big benefits that can positively affect the process and lessenthe probability of losing sales and profit.
Keywords: IT & Management